Age, Conditions and Sources of Igneous Rocks of Gora Rudnaya (Southern Yakutia) - V. E. Guzev; V. I. Leontiev; B. V. Belyatsky; A. V. Terekhov; A. V. Molchanov (Georesursy)
The paper presents the results of a complex petrogeochemical and isotope-geochemical (Rb–Sr and Sm–Nd systems) study of alkaline syenites and ore-bearing metasomatites (beresites) of the Gora Rudnaya (Southern Yakutia, Russia), as well as a comparison with compositionally similar massifs of the Aldan Mesozoic igneous province. The Gora Rudnaya, together with the recently discovered Morozkinskoye deposit, is located within the Central Aldan ore region. The massif is composed predominantly of alkaline syenites with a minor amount of alkaline porphyritic syenites, which are intruded by later dikes and sills of alkaline syenite porphyries and calc-alkaline lamprophyres. Industrial gold mineralization is confined to beresitization zones (Qz–Ser– Ank–Py) in areas of intense metasomatic reworking of rocks along steeply dipping fault structures within the intrusion. The obtained Rb–Sr age values for ore-bearing metasomatites (132±1 Ma) indicate subsynchronism of the ore process and crystallization of alkaline syenites, which corresponds to the time of manifestation of the main stage of magmatism in the Aldan Mesozoic igneous province (150–115 Ma). The rocks of the Gora Rudnaya do not differ in petrogeochemical and isotope-geochemical characteristics from rocks of similar composition from other massifs of the Aldan Mesozoic igneous province, indicating a wide lateral distribution of enriched EM I type mantle beneath the studied region. Variations in the initial isotopic composition of neodymium ((143Nd/144Nd) : from 0.511375 to 0.511636) in the studied samples are probably due to the heterogeneity of the source composition. At the same time, the calculated model ages indicate that the enriched mantle source was formed no later than 2.0–2.5 Ga.